Finite element analysis of headed studs embedded in thin UHPC. (October 2019) - Cao, Junhui; Shao, Xudong
Abstract: With an increasing use of ultra-high performance concrete (UHPC) in civil engineering, steel-concrete composite structures continue to progress. However, studies focusing on headed studs embedded in UHPC are limited, which hinders the design of steel-UHPC composite structures. This paper investigates the shear-resisting behavior of headed studs embedded in thin UHPC by using the finite-element (FE) analysis technique. A FE model was established for a push-out test, aiming to reflect the plastic behavior of the specimens and to evaluate the damage process in the headed studs and UHPC. The analysis results were compared to test results. It was revealed that the load-slip curve, shear strength, and failure mode all agreed well with the experimental observations. A parametric analysis was performed based on the validated FE model. The influence of stud diameter, stud height, and compressive strength of UHPC on the shear behavior of the headed studs was revealed. Further, the shear strengths obtained in the FE analysis were compared to the results predicted through theoretical equations. The comparison indicates that for headed studs embedded in UHPC, the contribution of the weld collar should be considered to evaluate the shear strength. Highlights: A 3-D nonlinear FE model was established for the push-out test. The analysis results agreed well with the test results. The effect of stud diameter, stud height, compressive strength of UHPC on the shear behavior of headed studs was revealed. The contribution of weld collar should be considered to predict of the shear strength for headed studs embedded in UHPC.